TREC10 Web and Interactive Tracks at CSIRO - Craswell, Nick; Hawking, David; Wilkinson, Ross; Wu, Mingfang (Proceedings of TREC-2001, 2001)
This year, CSIRO teams participated in all three tasks of the web track; these being: the automatic topic distillation task, the home/named page finding task and the interactive topic distillation task. This paper describes our approaches, experiments and results. The following section describes our experiments in the two automatic tasks, and Section 3 describes our experiment in the interactive task.
://research.microsoft.com/users/nickcr/pubs/craswell_trec01.pdf